SISTEM INFORMASI PENGOLAHAN DATA ASET HARDWARE DI KEMENTRIAN PERTANIAN DAN PERIKANAN TIMOR LESTE - MAIA, CUSTODIO JERONIMO; Mumpuni, Indah Dwi; Widayanti, Rahayu (DINAMIKA DOTCOM, 2015)
Since the formation of the Ministry of Agriculture and Fisheries of Timor Leste problem faced by the Ministry of Agriculture and Fisheries of Timor-Leste is the absence of a record of information systems, transaction manage hardware assets turnover and create reports necessary for the department. The purpose of this research is the establishment of an information system application data processing hardware assets in the ministry of agriculture and fisheries East Timor. This information system is built using Java script software, netbeans and use My SQL database. By using Java script, netbeans the development of this information system is fast and easy. Information Systems implements data processing hardware assets as may assist staff in the IT division of the ministry in the control of hardware assets are in use by employees and information systems can also be mendatakan all assets and computer hardware at the Ministry of Agriculture and Fisheries of Timor-LesteProcess usage of hardware assets in the Ministry of Agriculture and Fisheries of Timor Leste begins with data collection staff, then transferring assets hardware to staff, as well as mengortrol every weekday. Then make a report to the IT manager.Â Keywords: Information systems, hardware asset